The mathematical model of thermoelastic stresses in the Carpathian region - Bakhova Natalia (Russian Journal of Earth Sciences, 2022)
The two-dimensional thermoelastic model of the Carpathian region is constructed using the finite element method. The physical-mathematical model is as close as possible to the real environment. A~high-precision detailed distribution of temperatures, heat flow, thermoelastic stresses and displacements is obtained. It is shown that inhomogeneous heating of rocks and structural heterogeneities lead to significant changes in stress and displacement fields in the Carpathian region.